Nanoscale and functional heterogeneity of the hippocampal extracellular space - Grassi, Diego; Idziak, Agata; Lee, Antony; Calaresu, Ivo; Sibarita, Jean-Baptiste; Cognet, Laurent; Nägerl, U. Valentin; Groc, Laurent (Cell reports (Cambridge), 2023)
The extracellular space (ECS) and its constituents play a crucial role in brain development, plasticity, circadian rhythm, and behavior, as well as brain diseases. Yet, since this compartment has an intricate geometry and nanoscale dimensions, its detailed exploration in live tissue has remained an unmet challenge. Here, we used a combination of single-nanoparticle tracking and super-resolution microscopy approaches to map the nanoscale dimensions of the ECS across the rodent hippocampus. We report that these dimensions are heterogeneous between hippocampal areas. Notably, stratum radiatum CA1 and CA3 ECS differ in several characteristics, a difference that gets abolished after digestion of the extracellular matrix. The dynamics of extracellular immunoglobulins vary within these areas, consistent with their distinct ECS characteristics. Altogether, we demonstrate that ECS nanoscale anatomy and diffusion properties are widely heterogeneous across hippocampal areas, impacting the dynamics and distribution of extracellular molecules. [Display omitted] •Nanoscale map of the hippocampal formation extracellular space•The extracellular space characteristics differ between areas and layers•The CA1 stratum radiatum extracellular space is smaller but more fluid than in CA3•The extracellular space characteristics tune immunoglobulin distribution Grassi et al. describe the nanoscale organization of the extracellular space of the rodent hippocampus. Its physical properties differ strongly across the hippocampus, in particular between the stratum radiatum of CA1/3. These marked differences go hand in hand with differences in the dynamics and distribution of immunoglobulins in these areas.